Community engagement strategies to promote recruitment and participation in clinical research among rural communities: A narrative review. Issue 1 (8th February 2023) - Brockman, Tabetha A.; Shaw, Olivia; Wiepert, Liana; Nguyen, Quang Anh; Kelpin, Sydney S.; West, Ian; Albertie, Monica; Williams, Shantel; Abbenyi, Adeline; Stephenson, Noreen; Almader-Douglas, Diana; Patten, Christi A.
Abstract: Residents of rural areas are underrepresented in research. The aim of this narrative review was to explore studies describing the effectiveness of community engagement strategies with rural communities to promote participant recruitment and participation in clinical research. Following PRISMA guidelines, this narrative review was conducted in June 2020. Our search strategy was built around keywords that included community-engaged research, rural community, and recruitment strategies into clinical research. Content-related descriptive statistics were summarized. The selected articles were distributed into categories of levels of community engagement: inform, consult, involve, collaborate, or co-lead. The search resulted in 2, 473 identified studies of which forty-eight met inclusion criteria. Of these, 47.1% were randomized controlled trials. The most common levels of engagement were consultation (n = 24 studies) and collaboration (n = 15), while very few focused on informing (n = 2) and co-leadership (n = 2). Strategies, limitations, and findings are discussed for each level of community engagement. This narrative addressed a gap in knowledge regarding participant recruitment in rural communities in relation to assistance from community members. Community engagement contributed to the success of the research, especially in recruitment, participation, and building trust and partnership.